Prospective study on the role of preoperative mannitol in capsulorhexis and reducing intraoperative complications in primary angle-closure disease surgery - Zhiqiao Liang; Hongyan Li; Xianru Hou; Kangyi Yang; Kun Lv; Yao Ma; Ye Lu; Kuankuan Wu; Huijuan Wu (Journal of International Medical Research)
Objective To evaluate the effect of preoperative intravenous mannitol on the capsulorhexis process and intraoperative complications in patients with primary angle-closure glaucoma (PACG). Methods In this prospective randomized controlled trial, 65 PACG eyes were randomized into the mannitol and control groups. The capsulorhexis duration, number of forceps grasps, need for viscoelastic re-injection, and intraoperative complications were recorded. Results The mannitol group had a significantly shorter capsulorhexis duration and fewer forceps grasps of the capsule. All intraoperative complications (18.2%) occurred in the control group. The patients with intraoperative complications had significantly higher intraocular pressure and lower best-corrected visual acuity than those without complications after surgery. Multivariate analysis found that intravenous mannitol (odds ratio [OR] = −14.263; 95% confidence interval [CI] =−26.713 to −1.813) reduced the capsulorhexis duration, whereas zonulopathy (OR = 14.477, 95% CI = 2.622–26.331) prolonged the duration. Conclusion Preoperative intravenous mannitol can reduce the risk of intraoperative complications and improve postoperative outcomes in patients with PACG. Factors including anterior chamber depth, incision location and method, and the zonule status significantly influence the capsulorhexis process.